Site-specific modification and segmental isotope labelling of HMGN1 reveals long-range conformational perturbations caused by posttranslational modifications. Issue 2 (5th January 2021) - Niederacher, Gerhard; Urwin, Debra; Dijkwel, Yasmin; Tremethick, David J.; Rosengren, K. Johan; Becker, Christian F. W.; Conibear, Anne C.
Abstract : Using protein semi-synthesis, segmentally isotope-labelled variants of nucleosome-binding protein HMGN1 were generated with site-specific posttranslational modifications to explore their structural and functional effects. Abstract : Interactions between histones, which package DNA in eukaryotes, and nuclear proteins such as the high mobility group nucleosome-binding protein HMGN1 are important for regulating access to DNA. HMGN1 is a highly charged and intrinsically disordered protein (IDP) that is modified at several sites by posttranslational modifications (PTMs) – acetylation, phosphorylation and ADP-ribosylation. These PTMs are thought to affect cellular localisation of HMGN1 and its ability to bind nucleosomes; however, little is known about how these PTMs regulate the structure and function of HMGN1 at a molecular level. Here, we combine the chemical biology tools of protein semi-synthesis and site-specific modification to generate a series of unique HMGN1 variants bearing precise PTMs at their N- or C-termini with segmental isotope labelling for NMR spectroscopy. With access to these precisely-defined variants, we show that PTMs in both the N- and C-termini cause changes in the chemical shifts and conformational populations in regions distant from the PTM sites; up to 50–60 residues upstream of the PTM site. The PTMs investigated had only minor effects on binding of HMGN1 to nucleosome core particles, suggesting that they have other regulatory roles. This study demonstrates the power of combining protein semi-synthesis for introduction of site-specific PTMs with segmental isotope labelling for structural biology, allowing us to understand the role of PTMs with atomic precision, from both structural and functional perspectives.